2015
DOI: 10.1039/c5cc06961k
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids as an electrolyte for the electro synthesis of organic compounds

Abstract: The use of ionic liquids (ILs) as a solvent and an electrolyte for electro organic synthesis has been reviewed. To date several ILs exist, however the ILs based on tetraalkylammonium, pyrrolidinium, piperidinium and imidazolium cations with BF4(-), PF6(-), and TFSI anions have been widely used and explored the most. Electro organic synthesis in ionic liquid media leading to the synthesis of a wide range of organic compounds has been discussed. Anodic oxidation or cathodic reduction will generate radical cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 161 publications
0
39
0
Order By: Relevance
“…Room temperature ionic liquids (RTILs) or low temperature molten salts [1] have emerged as promising media to improve performance in electrochemical applications and devices. In particular, RTILs provide new interesting results in electrochemical sensors [2,3], electrosynthesis of organic compounds via alternative routes [4] and synthesis of functional materials with imidazolium-based RTILs for various and relevant applications [5][6][7][8]. In addition to this, the use of RTILs in the field of energy conversion and storage is a promising field, for instance, in redox flow batteries [9], supercapacitors [10] and electrocatalytic reactions such as oxygen reduction reaction [11], CO electrooxidation [12][13] and CO 2 electroreduction [14][15][16][17][18], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Room temperature ionic liquids (RTILs) or low temperature molten salts [1] have emerged as promising media to improve performance in electrochemical applications and devices. In particular, RTILs provide new interesting results in electrochemical sensors [2,3], electrosynthesis of organic compounds via alternative routes [4] and synthesis of functional materials with imidazolium-based RTILs for various and relevant applications [5][6][7][8]. In addition to this, the use of RTILs in the field of energy conversion and storage is a promising field, for instance, in redox flow batteries [9], supercapacitors [10] and electrocatalytic reactions such as oxygen reduction reaction [11], CO electrooxidation [12][13] and CO 2 electroreduction [14][15][16][17][18], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Due to specific physicochemical properties, they are able to increase both the reactivity and/or selectivity of a number of industrially important processes . The use of ILs as a solvent and an electrolyte has been shown to be successful for electro organic synthesis . To date the ILs based on piperidinium, tetraalkylammonium, pyrrolidinium, and imidazolium cations with [BF 4 ] – , [PF 6 ] – , and [NTf 2 ] – anions have been explored and widely used the most.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The use of ILs as a solvent and an electrolyte has been shown to be successful for electro organic synthesis. [2] To date the ILs based on piperidinium, tetraalkylammonium, pyrrolidinium, and imidazolium cations with [BF 4 ] -, [PF 6 ] -, and [NTf 2 ]anions have been explored and widely used the most. In the focus of current study are pyridinium based ILs with the BF 4 anion.…”
Section: Introductionmentioning
confidence: 99%
“…Tajima, Fuchigami and co-workers showed that also solid-supported bases could serve as a similar solution by in situ generation of the electrolyte from methanol or HFIP as multifunctional solvents [201,202,203,204]. Ionic liquids can also be used as the solvent as well as the electrolyte in electrosynthesis [205,206].…”
Section: Discussionmentioning
confidence: 99%